The Development Strategy of Human Resources Management In Children's Social Welfare Institution (LKSA) (Case Study in LKSA AL-Mubaraak Orphanage Bengkulu - Emilda Sulasmi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to explain how the strategy for developing human resources at the Child Welfare Institution (LKSA) by taking a case at the Al-Mubarak LKSA Orphanage in Bengkulu City. The method used is a qualitative research method with a descriptive approach, the source of this research data is the manager and caregiver of LKSA Al-Mubarak Bengkulu City and also the document data obtained through the Social Service of Bengkulu City. The results showed that the Human Resources (HR) Child Welfare Institution in Bengkulu, especially the Al-Mubarak Orphanage did not meet social ministerial regulations Number 108 / HUK / 2009 regarding Certification for Professional Social Workers and Social Welfare Workers. Furthermore also found several aspects that have not met the care standards according to the Republic of Indonesia Minister of Social Affairs Regulation Number 30 of 2011. As a suggestion from the author, the Child Welfare Institution should work with the Social Service to identify social workers who work at the Child Welfare Institution or at the Office Social who has supervisory competence and set him as a supervisor of the Child Welfare Institution.